Subtyping Obsessive-Compulsive Disorder: Neuropsychological Correlates - Catherine L. Harris; Wayne M. Dinn (Behavioural Neurology)
We administered neuropsychological measures considered sensitive to prefrontal dysfunction (both orbitofrontal and dorsolateral prefrontal neocortex) to obsessive-compulsive disorder (OCD) patients and control subjects. OCD subjects exhibited performance deficits, in comparison to community controls, on three measures sensitive to orbitofrontal neocortex dysfunction. Contrary to expectation, OCD patients also exhibited performance deficits on measures sensitive to dorsolateral prefrontal neocortex dysfunction. However, distinct neurocognitive profiles emerged when we examined the impact of comorbid schizotypal personality features on neuropsychological test performance. Primary OCD patients displayed impaired performance on measures sensitive to orbitofrontal dysfunction; however, they did not differ from control subjects on tests of dorsolateral function. OCD subjects presenting with schizotypal personality features performed poorly not only on tests sensitive to orbitofrontal dysfunction, but also on tests sensitive to dorsolateral dysfunction. Findings suggest that OCD can be subdivided into clinical subtypes, and distinct prefrontal subsystems may be differentially involved in these subtypes.